Generation and verification method of trusted signature seal incorporating handwriting features - Li LI; Shang GAO; Peiliang ZUO; Jiazheng XUAN; Han SONG (网络与信息安全学报, 2024)
With the rapid development of electronic communication and internet technology, the digitization of document circulation and processing has become increasingly prevalent.The trend towards greater convenience, flexibility, and diversity in electronic document signing is evident through practices such as online signature collection, remote signature confirmation, and electronic signature authentication.However, the signing and verification processes face challenges related to authenticity, integrity, and more.Instances of unlawful entities intercepting, copying, and forging signature images using low-cost methods to sign documents with false identities, as well as tampering with and forging signature files, are common.The application of electronic signature systems also encounters obstacles such as high costs, limited deployment, lack of universality, and complexities in real-time and consistent verification.To address these risks and challenges and ensure reliable verification in personal document signing processes, a credible method for generating and verifying signature seals that integrate handwriting features was proposed.This method primarily utilized the facial recognition and identity information matching functions of a trusted identity authentication platform.It integrated signature handwriting features and uniquely bound them to the signer's identity for reliable authentication.Accordingly, a signature seal with integrated handwriting features, a verification link for the signed document, and a digital signature QR code were generated.Analysis indicates that the signature seal produced by the proposed method not only serves the purpose of identity verification but also enables the discernment of the authenticity of the signed document.The verification link embedded in the QR code can directly validate the signer's identity, handwriting, and the authenticity and consistency of the signed document through online channels, providing a convenient means for the verification of both electronic and paper documents.The proposed method holds broad application prospects in the fields of electronic document circulation and the verification of the authenticity of electronic and paper documents.